The Cage-maker : A Novel - Seitz, Nicole A. (Book collections on Project MUSE., 2017)
"Author's Note Dear Reader, I, too, love a good story, which is why I got hooked on this one. When researching my own family history in New Orleans, I ran across a great-grandfather who was a birdcage maker at 47 St. Ann Street and another great-granduncle who married a young heiress named Carmelite. She died only nine months later, and I found I could not stop digging until I knew the truth of her demise. Was her husband, my ancestor, Ferdinand, involved in any way, or did she die naturally? And why had they eloped when she was only fifteen years old? I began to find Louisiana Supreme Court cases detailing a complex mystery of love, fortune, and deceit. I stumbled upon a money trail and followed it all the way back to an adulteress in Havana. Heir after heir of this great New Orleans wealth met with death or disaster soon after receiving the inheritance. There was talk of voodoo. A young murderer spoke of a curse on his money. And when the younger sister died after eloping only a year before, just as her sister had done, I watched as her father again went to court in search of the money. So you see, I had to keep going, although I didn't know what I would or even hoped to find"--